(untitled) (Rajarshi Janak University Research Journal, 2025)
This study evaluated the drinking water quality of hand pumps in Bideha and Sahidnagar Municipalities, Nepal, in relation to the Nepal Drinking Water Quality Standards (NDWQS), 2022. In a cross-sectional design, 14 groundwater samples were analyzed using standard methods for physicochemical parameters: pH, turbidity, electrical conductivity (EC), ammonia, chloride, and alkalinity. The findings indicated that all tested parameters conformed to NDWQS limits. The recorded ranges were: pH (6.59–7.19), turbidity (0.1–3.1 NTU), EC (236–570 µS/cm), ammonia (0.21–1.45 mg/L), chloride (15.88–24.84 mg/L), and alkalinity (16–32 mg/L). These values are under NDWQS limits, however ammonia concentration in Ekarahi and Navtoli are approaching the borderline. The study highlights the crucial need for ongoing monitoring, improved sanitation, and community education to ensure the safety of drinking water in these areas.